Induced mutations in French bean (Phaseolus vulgaris L.) affecting seedcoat colour - V. S. Kothekar, S. E. Mahamune* and (Journal of Experimental Sciences, 2010)
Ethyl methanesulphonate (EMS) concentrations of 0 (control), 0.05%, 0.10% and 0.15% were applied to dormant seeds ofÂ Â  Phaseolus vulgaris L. cv. Varun. Mutations affecting seed coat colour were detected in M2 generation. Highest mutation frequency was induced by 0.10% EMS. The seed coat colour mutants showed diverse shades of colour.